The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1007/s00167-018-4953-z
|View full text |Cite
|
Sign up to set email alerts
|

Cost-effectiveness analysis of surgical versus non-surgical management of acute Achilles tendon ruptures

Abstract: PurposeAn Achilles tendon rupture is a common injury that typically affects people in the middle of their working lives. The injury has a negative impact in terms of both morbidity for the individual and the risk of substantial sick leave. The aim of this study was to investigate the cost-effectiveness of surgical compared with non-surgical management in patients with an acute Achilles tendon rupture.MethodsOne hundred patients (86 men, 14 women; mean age, 40 years) with an acute Achilles tendon rupture were r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
49
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(50 citation statements)
references
References 26 publications
0
49
0
Order By: Relevance
“…Research [14,15,28,43] has shown the aforementioned factors to be important factors in influencing patient outcomes and the reporting of these aspects should be encouraged within the scientific literature. It must be acknowledged that there are still multiple factors capable of impacting on patient outcomes which were not controlled in the current study including the degree of tendon separation prior to surgery [48], the magnitude of tendon elongation post-surgery [32] Tables Table 1. Descriptive statistics (mean [standard deviation]) for the 10 items in the ATRS along with the total score. r values depict the relationship between each ATRS item and months since surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Research [14,15,28,43] has shown the aforementioned factors to be important factors in influencing patient outcomes and the reporting of these aspects should be encouraged within the scientific literature. It must be acknowledged that there are still multiple factors capable of impacting on patient outcomes which were not controlled in the current study including the degree of tendon separation prior to surgery [48], the magnitude of tendon elongation post-surgery [32] Tables Table 1. Descriptive statistics (mean [standard deviation]) for the 10 items in the ATRS along with the total score. r values depict the relationship between each ATRS item and months since surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Acute Achilles tendon rupture poses a substantial socioeconomic burden,1 affecting work-active adults and with an incidence of 20–32 per 100 000 per year 2 3. Results of treatment are unsatisfactory, as one out of three patients end up with poor outcome after treatment4 5 and the deficits persist for many years 6…”
Section: Introductionmentioning
confidence: 99%
“…Prior to this study, there have only been a few health-economic studies that have evaluated the economic cost of Achilles tendon ruptures. Truntzer et al [ 25 ] and Westin et al [ 27 ] have evaluated whether operative or nonoperative treatment is economically favorable when it comes to Achilles tendon ruptures. Moreover, Carmont et al [ 4 ] compared the economic impact of the open and percutaneous repair of Achilles tendon ruptures.…”
Section: Discussionmentioning
confidence: 99%
“…The health-care costs used in this study are presented in Table 1 . The data was later compared with statistics from the economic study performed by Westin et al [ 27 ]. In that study, the economic cost of the operative and nonoperative treatment of acute Achilles tendon ruptures at the same Sahlgrenska University Hospital between 2009 and 2010 were analyzed.…”
Section: Methodsmentioning
confidence: 99%